Terapi komplementer non invasif pada peningkatan status kesehatan sistem pernapasan penderita PPOK: Sebuah literature review - Senja Paramita; I Made Kariasa; Sri Yona (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2021)
Non-invasive complementary therapies in improving the health status of the respiratory system in patients with COPD: A literature review Background: Patients with COPD need an individual treatment plan that aims to cope with symptoms and requires a different and individualized treatment plan. The medication and surgery cause several complications, accompanied by negative side effects, the “one size fits all as a universal approach